Prescription opioid use patterns, use disorder diagnoses and addiction treatment receipt after the 2014 Medicaid expansion in Oregon. (30th June 2019) - Springer, Rachel; Marino, Miguel; Bailey, Steffani R.; Angier, Heather; O'Malley, Jean P.; Hoopes, Megan; Lindner, Stephan; DeVoe, Jennifer E.; Huguet, Nathalie
Abstract: Background/Aims: Evidence suggests that Medicaid beneficiaries in the United States are prescribed opioids more frequently than are people who are privately insured, but little is known about opioid prescribing patterns among Medicaid enrollees who gained coverage via the Affordable Care Act Medicaid expansions. This study compared the prevalence of receipt of opioid prescriptions and opioid use disorder (OUD), along with time from OUD diagnosis to medication‐assisted treatment (MAT) receipt between Oregon residents who had been continuously insured by Medicaid, were newly insured after Medicaid expansion in 2014 or returned to Medicaid coverage after expansion. Design: Cross‐sectional study using inverse‐propensity weights to adjust for differences among insurance groups. Setting: Oregon. Participants: A total of 225 295 Oregon Medicaid adult beneficiaries insured during 2014–15 and either: (1) newly enrolled, (2) returning in 2014 after a > 12‐month gap or (3) continuously insured between 2013 and 2015. We excluded patients in hospice care or with cancer diagnoses. Measurements: Any opioid‐dispensed, chronic (> 90‐days) and high‐dose (> 90 daily morphine milligram equivalence) opioid use, documented OUD diagnosis and MAT receipt. Findings: Compared with the continuously insured, newly and returning insured enrollees were less likely to be dispensed opioids [newly: 42.3%, 95% confidence interval (CI) = 42.0–42.7%; returning: 49.3%, 95% CI = 48.8–49.7%; continuously: 52.5%, 95% CI = 52.0–53.0%], use opioids chronically (newly: 12.8%, 95% CI = 12.4–13.1%; returning: 11.9%, 95% CI = 11.5–12.3%, continuously: 15.8%, 95% CI = 15.4–16.2%), have OUD diagnoses (newly: 3.6%, 95% CI = 3.4–3.7%; returning: 3.9%, 95% CI = 3.8–4.1%, continuously: 4.7%, 95% CI = 4.5–4.9%) and receive MAT after OUD diagnosis [hazard ratio newly: 0.57, 95% CI = 0.53–0.61; hazard ratio returning: 0.60, 95% CI = 0.56–0.65 (ref: continuously)]. Conclusions: Residents of Oregon, United States who enrolled or re‐enrolled in Medicaid health insurance after expansion of coverage in 2014 as a result of the Affordable Care Act were less likely than those already covered to receive opioids, use them chronically or receive medication‐assisted treatment for opioid use disorder.